2019
DOI: 10.1007/s10461-019-02404-z
|View full text |Cite
|
Sign up to set email alerts
|

MSM Behavior Disclosure Networks and HIV Testing: An Egocentric Network Analysis Among MSM in China

Abstract: Men who have sex with men (MSM) disclose same-sex behaviors with others, creating disclosure networks. This study examined the characteristics of disclosure networks that are associated with HIV testing among MSM in China through an online nationwide survey. Name-generator questions were used to ask each participant ("ego") to nominate up to five social network members ("alters") with whom he had disclosed same-sex behaviors. Among the 806 men, the average disclosure network size was 4.05. MSM who reported lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
1
17
0
1
Order By: Relevance
“…Finally we found that MSM who had disclosed their sexual behavior to someone (non-specific disclosure) or their healthcare provider (outside the study context) were more likely to select rectal STI testing compared to urethral testing. Past China research indicated that larger disclosure networks were associated with greater propensity of HIV testing [28,18]. Increased probability of never testing for HIV or syphilis was associated with non-disclosure to anyone or health professionals [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally we found that MSM who had disclosed their sexual behavior to someone (non-specific disclosure) or their healthcare provider (outside the study context) were more likely to select rectal STI testing compared to urethral testing. Past China research indicated that larger disclosure networks were associated with greater propensity of HIV testing [28,18]. Increased probability of never testing for HIV or syphilis was associated with non-disclosure to anyone or health professionals [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally we found that MSM who had disclosed their sexual behavior to someone (non-specific disclosure) or their healthcare provider (outside the study context) were more likely to select rectal STI testing compared to urethral testing. Past China research indicated that larger disclosure networks were associated with greater propensity of HIV testing [18,28]. Increased probability of never testing for HIV or syphilis was associated with non-disclosure to anyone or health professionals [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Option four indicates disclosure to health providers, which is key to receiving appropriate healthcare [27], more so than the other group specific disclosure options. For example, men out to their healthcare provider are more likely to get HIV testing compared to those out to their family [28]. Although participants attended a specialized MSM testing clinic, this does not reflect their disclosure to their primary care or other health providers.…”
Section: Methodsmentioning
confidence: 99%
“…Facility-based testing or self-testing history of syphilis, HIV and other STIs, and treatment experience will also be collected. A set of questions including a scale to measure social support, community leadership, and the size of their social network will be asked [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%